Properties of Thermally Modified Southern Pine Wood Pretreated with Alkylalkoxysilanes - Cong Chen; Wang Wang; Jinzhen Cao; Qi Qi; Wenbo Ma (BioResources, 2016)
The alkyl-alkoxysilane (AAS) pre-impregnation method and thermal modification were combined to improve the water-related properties of southern yellow pine (Pinus spp.) sapwood. Four types of AAS with varied alkyl chain lengths, including butyltrimethoxysilane (BTMOS), octyltrimethoxysilane (OTMOS), dodecyltrimethoxysilane (DTMOS), and cetyltrimethoxysilane (CTMOS), were used to pre-impregnate wood samples at a concentration of 5% or 15% mass fraction, and the subsequent thermal modification was processed at either 180 °C or 200 °C. The water absorption, dimensional stability, equilibrium moisture content (EMC), mechanical properties (modulus of rupture (MOR), and modulus of elasticity (MOE)), and mold resistance of the treated wood were evaluated. Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were used to reveal the mechanism of the combined treatments in improving the properties of wood. Compared with thermal modification alone, the AAS combined treatment improved the water repellency, mechanical properties, and mold resistance of the modified wood. The study also identified the penetration of AAS into the wood cell wall and its reaction with the chemical components of the cell wall.